A total systems study on Fashion View - Abuan, Victoria Jane T.; Go, Raymond C.; Ramos, Kiert John A.; Sy, Ian Angelo F.
Fashion View has been in the garments industry for 12 years, specializing in made-to-order products. Its operations targets to produce 4-5 sets of uniforms for 150-350 employees of 2-3 clients monthly, earning PhP 10 million in sales annually. From 2007-2011, net income has been growing from about 4% to 17% throughout the whole period. There is an increase in both the revenue and expenses at different rates. Despite these, Fashion View's profit is below the 35% standard for the garments industry. Analyses done on the company's operations and business processes reveal that profit earned is affected by the direct costs, consisting of labor and material costs; the overhead costs; and the unit price. These factors yielded significant effects to the profit being earned by company. With profit levels averaging 10%, improvements in these factors were formulated and identified in order to increase profits. Further evaluation of the different factors pointed out to the three critical alternatives that would significantly affect profit: set target number of clients and items; increase outside sewers; and unit price increase. Major focus is given to the reduction of overhead costs through setting of target number of clients and items as this was identified to have the largest contribution to the increase in profit. Four proposals were developed around the manipulation of the critical alternatives. Each proposal yielded a significant increase in profit depending on the combination of the alternatives. Fashion View may implement any of these proposals depending on the target increase in profit in mind.